Analisis Kerusakan Pada Permukaan Roda Kereta Rel Listrik - Muhammad Ardiansyah; Dwi Rahmalina (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa dan Inovasi, 2023)
The wheels of electric rail cars are an essential component of rail transportation when they are in use. At the time of inspection, the technician discovered damage to the wheel's surface. This is due to the hardening of the brake block, which damages the wheel's surface. This research was conducted with the purpose of analyzing the causes of damage to the tread surface of the wheels and identifying a suitable replacement for the original brake block, which is no longer manufactured and has been replaced by imitation block brakes. so that further action can be taken to prevent similar occurrences in the future. Using the Vickers hardness test indentation method, the purpose of this study is to examine various heat treatments for determining a material's hardness level. The test results indicate that the VHN value increases with increasing heating temperature. The original specimen produced 99.5 VHN in the first test without heat treatment, while the X block brake produced 26.9 VHN and the Y brake produced 136.0 VHN. The second test with 200°C heat treatment on the original specimen yielded 96.8 VHN, 73.1 VHN from the X block, and 152.9 VHN from the Y block. In addition, the third test with 400°C heat treatment on the original specimen produced 92.4 VHN, 47.8 VHN for the X block brake, and 268.3 VHN for the Y block brake. The Vickers Hardness Test (VHN) hardness value is affected by heat treatment; the higher the heating value, the higher the hardness value of the remolok specimen.